Introduction: the new stylism. Issue 6 (3rd June 2021) - Masters, Ben
ABSTRACT : To theorise style and stake its value seem more than ever urgent matters. This article suggests that a 'style consciousness' has become prevalent in criticism of different kinds – from the scholarly to the creative to the essayistic – where style has re-emerged as a central critical concern; and that contemporary critical discussion of style is where problematized considerations like technique, authorial intention and aesthetic evaluation are being qualified and restored to critical centrality through their meeting with the political, ethical and social. It then locates the articles that make up this special issue within current debates and diverse ways of thinking about style. In doing so it identifies a 'new stylism' – a term it uses very broadly to describe how contemporary critics are marrying attention to the ideological contexts of literature with aesthetic concerns, thus turning style consciousness away from negative connotations of superficiality, shallowness, and naivety, towards political and ethical engagement.